Exploring Challenges in Applying the Merdeka Curriculum at Schools - Hanayanti, Hanayanti; Tahapary, Nancy L.; Basalama, Popi N.; Miniaty, Yuni (Program Studi Pendidikan Bahasa Inggris Kabupaten Kepulauan Aru, 2023)
The study aimed to analyze existing literature, shedding light on challenges encountered in its application. Tracing the historical context, the study explored the origin, growth, and evolution of the Merdeka Curriculum. Identified challenges primarily revolve around teacher-related issues, resource constraints, and assessment concerns. Teacher-related challenges include insufficient training and a lack of preparedness for changes in teaching methods. Resource constraints encompass limited teaching materials and inadequate infrastructure and technology support. Assessment concerns revolve around difficulties in measuring holistic development and aligning assessments with curriculum goals. To address these challenges, the article outlines strategies derived from existing literature, featuring successful case studies and best practices, alongside policy implications and potential reforms. Additionally, the article explores future directions and research gaps, suggesting areas for further study, ongoing improvement strategies, and potential policy changes to mitigate identified challenges. This review aims to contribute valuable insights to educators, policymakers, and researchers involved in the implementation and refinement of the Merdeka Curriculum.